People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Stress Testing the Banking Sector-Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Stress Testing the Banking Supervision was prepared in the context of the Financial Sector Assessment Program (FSAP) for the People's Republic of China-Hong Kong Special Administrative Region (HKSAR). Bank liquidity tests focus on sudden, sizable withdrawals of funding and the sufficiency of existing assets to withstand those shocks under stressed conditions. The stress test results confirm a high degree of resilience of the sector. This reflects the strength of the banks at the starting position, which reduces their fundamental vulnerability to shocks. Banks in HKSAR hold very high levels of capital, are very profitable, and have a low level of asset impairments amid stable funding profiles. The Hong Kong Monetary Authority is encouraged to continue its integration of risk-based supervision in the development of stress test scenarios for macroprudential policy and surveillance. Banking supervisors routinely conduct stress tests and, from time to time, modify relevant assumptions in order to support thematic reviews of identified vulnerabilities against emerging risks.